2010
DOI: 10.1128/aem.01219-09
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Acid Tolerance of Campylobacter jejuni through Coincubation with Amoebae

Abstract: Campylobacter jejuni is a recognized and common gastrointestinal pathogen in most parts of the world. Human infections are often food borne, and the bacterium is frequent among poultry and other food animals. However, much less is known about the epidemiology of C. jejuni in the environment and what mechanisms the bacterium depends on to tolerate low pH. The sensitive nature of C. jejuni stands in contrast to the fact that it is difficult to eradicate from poultry production, and even more contradictory is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 39 publications
0
27
0
3
Order By: Relevance
“…Acidic conditions may trigger the activation of C. jejuni virulence phenotypes in preparation for host cell invasion. One study investigating co-incubation of C. jejuni with amoebae demonstrated that incubation of C. jejuni under mildly acidic conditions increased its adherence to and invasion of amoebae [37]. The same study also reported that bacterial survival increased after long-term acid exposure and that incubation of C. jejuni with low pH for 1 h increased motility on a swarm plate.…”
Section: Discussionmentioning
confidence: 96%
“…Acidic conditions may trigger the activation of C. jejuni virulence phenotypes in preparation for host cell invasion. One study investigating co-incubation of C. jejuni with amoebae demonstrated that incubation of C. jejuni under mildly acidic conditions increased its adherence to and invasion of amoebae [37]. The same study also reported that bacterial survival increased after long-term acid exposure and that incubation of C. jejuni with low pH for 1 h increased motility on a swarm plate.…”
Section: Discussionmentioning
confidence: 96%
“…are ubiquitous in the environment and have been isolated from soil (Chai et al 2009), mud (Stuart et al 2010), bathing beach sand (Bolton et al 1999), and environmental water (Kemp et al 2005). Campylobacter has been associated with soil amebas that may provide a protected environment for the bacteria (Baré et al 2010;Axelsson-Olsson et al 2010). Campylobacter has also been detected in untreated tap water, consumption of which resulted in outbreaks of campylobacteriosis (Jakopanec et al 2008;Vogt et al 1982).…”
Section: Ecology Ecology Of Campylobactermentioning
confidence: 98%
“…(Axelsson-Olsson et al, 2010b;Baré et al, 2010). Axelsson-Olsson and co-authors investigated whether internalization of C. jejuni by Acanthamoeba affects bacterial tolerance to low pH.…”
Section: Interaction Between Acanthamoeba and Campylobactermentioning
confidence: 99%